Attentional bias modification with a new paradigm: The effect of the Detection Engagement and Savoring Positivity (DESP) task on eye-tracking of attention. (September 2020) - Corman, Maya; Aubret, Deborah; Ghazal, Joanne; Berthon, Mickael; Chausse, Pierre; Lohou, Christophe; Dambrun, Michaël
Abstract: Background and objectives: We tested the effect of a new Attentional Bias Modification (ABM) task - the Detection Engagement and Savoring Positivity (DESP) task - on attentional biases. The DESP is innovative in that it involves a procedure of savoring the positivity of various pictures. Methods: Participants were randomly assigned to the DESP or to a placebo control condition (experiment 1; n = 38) or a condition controlling for savoring (experiment 2; n = 54) in a pre-post/training experimental design. During one week, the participants completed the DESP or the control task once a day between three and six times. We assessed the effects of the DESP task on various attentional biases (i.e. positive, negative and threat) by computing dwell time from an eye-tracking technology before and after the training, and also one week after the post-training session in experiment 2. Results: In both experiments, the attentional bias toward positive stimuli between the pre- and the post-training increased significantly more in the DESP task condition than in the control conditions. Negative and threat attentional biases were not significantly affected by the experimental manipulations. Experiment 2 revealed that the DESP task – including the savoring instruction – increased significantly more the positive attentional bias than a task excluding this step and that this effect remained significant one week after the post-training session. Limitations: Our samples were mainly composed of women participants. This prevents generalization of the findings. Conclusions: The DESP task offers promising perspectives for sustainably improving attention to positive information. Highlights: Addresses the effects of ABM on Eye-Tracking of Attention. Tests a new ABM; the Detection Engagement and Savoring Positivity (DESP) Task. The DESP task increases the positive attentional bias toward positive stimuli. The savoring instruction embedded in the DESP task is an active ingredient. The DESP task's effect remains significant even one week after the training.